Pengaruh Sugesti Imajinasi Dengan Teknik Hypnoteaching Terhadap Keterampilan Menulis Cerpen - Pasoloran, Resli; Gasong, Dina; Dewi, Resnita (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to find out whether there is an effect of applying the imagination suggestion method with hypnoteaching techniques to improve students' short story writing skills at SMPN 2 Rantepao and whether the application of this method is effective in stimulating students' creative ideas in writing short stories. The type of research used is quantitative research with a quasi-experimental research design. Data collection procedures were carried out using test, questionnaire, observation and treatment methods. Data analysis techniques using test result data management and statistical analysis. The research results found in this study can be concluded that the two classes as well as the pretest and posttest data are samples that are not normally distributed. Paired Sample Test Results t Test obtained Sig. (2-Tailed) of 0.000<0.005 in the control class and 0.000<0.005 for the experimental class, so it can be concluded that there is a difference in the average pretest and posttest learning outcomes in the two classes. Based on the Independent Sample Test, data was obtained that there was an average or mean value in the experimental class posttest of 83.66 and 76.54 in the control class. This value can be interpreted as the average value in the experimental class being higher than the control class. Thus hypothesis H0 is rejected and hypothesis H1 is accepted.